Democracy Deficits, Inequality and Pollution. A Politico-Economic Analysis - Thomas Drosdowski (Universität Hannover, Wirtschaftswissenschaftliche Fakultät, 2005)
The article examines conditions, under which the degree of democratization influences environmental policy outcomes, with a given resource endowments' heterogeneity as a crucial feature of a politico-economic process. We develop an OLG model with pollution as an aggregate externality. The decisive voter chooses redistribution contributing to abatement financing. By comparing the optimal taxation under alternative political regimes we analyze their implications for environment, efficiency and growth. We find that left regimes, choosing more progressive redistribution, maintain better environmental quality, which supports empirical research. Inequality does not appear to be harmful for the environment, and it dampens the effect of democracy imperfections on redistribution.
Keywords: Q58; D72; D63; D31; Q53; H23; 330; Pollution; Political Economy; Inequality; Redistribution; Growth